Fatal cardiovascular instability secondary to hypercalcaemia and intracellular calcium deposition complicating T-cell leukaemia-lymphoma. (5th April 2016) - Shepherd, Stephen J; Wong, Davina; Mahadeva, Ula; Goldsmith, David; Shankar-Hari, Manu; Ostermann, Marlies
Adult T-cell leukaemia-lymphoma is a rare haematological malignancy, which can cause severe hypercalcaemia and metastatic calcification resulting in life-threatening arrhythmias.